European Works Council developments before, during and after the crisis - Kerckhofs, Peter (Luxembourg, 2015)
"European Works Councils (EWCs) provide an important vehicle for transnational information and consultation in multinational companies. This report explores the efforts of 10 EWCs to make these bodies optimally fit for purpose for European company level social dialogue. Looking at the developments in EWCs over a longer period of time gives an insight into the practices and possibilities that are realised in some of the EWCs. Based on these 10 longitudinal case studies, a comparative analysis explores the factors that can influence these developments and assesses the impact of the economic and financial crisis and of the recast directive 2009/38/EC. Other factors, such as company characteristics and whether these can influence developments in the composition or functioning of EWCs, are also examined."